Rosemary has immunosuppressant activity mediated through the STAT3 pathway. (October 2018) - von Schönfeld, Charlotte; Huber, Roman; Trittler, Rainer; Kammerer, Bernd; Garcia-Käufer, Manuel; Gründemann, Carsten
Graphical abstract: Highlights: In Europe extracts of Rosmarinus officinalis were traditionally used for the treatment of inflammatory diseases, like rheumatic arthritis. Extracts of Rosmarinus officinalis were investigated on human lymphocytes, because these cells are important inducers of rheumatic diseases. Rosmarinus officinalis inhibited proliferation of human lymphocytes and CD4 + T-cells in a dose-dependent manner. The immunosuppressive effect of Rosmarinus officinalis is mostly due to the effect of trans-caffeic acid through the STAT3 signaling pathway. Abstract: Objective: In Europe extracts of Rosmarinus officinalis were traditionally used for the treatment of rheumatic diseases. We investigated the capacity of standardized aqueous extracts of Rosmarinus officinalis on human primary lymphocyte function in vitro, as activated lymphocytes are an important mediator of rheumatic diseases. Methods: Lymphocyte proliferation was measured using membrane-permeable dye carboxyfluorescein diacetate succinimidyl ester (CFSE). Apoptosis was analysed by surface staining of phosphatidylserine (annexin V-assay) and necrosis was analysed by staining with propidium iodide. Modification of cell activity was detected by surface staining of CD69 and CD25. The activity of STAT3 in T-lymphocytes was determined by intracellular staining of STAT3 molecules. All endpoints were analyzed by using flow cytometry. The Rosmarinus officinalis extract was investigated at concentrations of 0.05–25 mg/mL. Analysis of the extract was performed using HPLC methods. Results: Rosmarinus officinalis inhibited proliferation of human lymphocytes and CD4 + T-cells in a dose-dependent manner (3.1–25 mg/mL) through induction of apoptosis. The intracellular signalling pathway STAT3 in T-cells, but not NF-kappaB and ERK1/2 in T- and B-cells was inhibited in a dose-dependent manner by Rosmarinus officinalis (0.2-6.2 mg/mL). Rosmanol, carnosolic acid, carnosol and trans-caffeic acid were tested in the same cellular models as the crude extract. From these, only trans-caffeic acid inhibited lymphocyte proliferation and STAT3 (30–100 μg/mL). Trans-caffeic acid was found in the extract in a concentration of 14.7 μg/mL. Conclusions: We conclude that an immunosuppressive effect of Rosmarinus officinalis is mostly due to the effect of trans-caffeic acid. It results in inhibition of the activity of STAT3 causing induction of apoptosis and inhibition of proliferation of T-lymphocytes.